Assorted functionality-appended UiO-66-NH2 for highly efficient uranium(vi) sorption at acidic/neutral/basic pH. Issue 25 (9th April 2020) - Tripathi, Sarita; Sreenivasulu, B.; Suresh, A.; Rao, C. V. S. Brahmmananda; Sivaraman, N.
Abstract : Eight assorted functionalities were anchored on UiO-66-NH2 via PSM strategy displaying MOFs with similar framework but variable uranyl binding affinities. The excellent sorption capacity of UiO-66-PO-Ph makes it efficient uranium sorbent material. Abstract : A series of functionalized metal organic frameworks (MOFs) were synthesized by the post-synthetic modification (PSM) of Zr(iv )-containing UiO-66-NH2 MOFs using covalent grafting with various functional groups utilizing pendant –NH2 moieties. The tethering of amide (with/without pendant carboxylic acid), iminopyridine, phoshinic amide and sulphur-containing functionalities produced a library of eight different UiO-66-NH2 derivatives. The functionalized MOFs were characterized by FT-IR spectroscopy, NMR, PXRD, TGA, SEM-EDX and BET surface area analysis. Uranyl ion extraction with the functionalized MOFs was investigated in acidic/neutral/basic conditions (pH 1 to 9). This work presents a comprehensive study of different functionalized MOFs to investigate the effects of various analytical parameters, including pH, contact time, and desorption process. The MOFs as solid phase extractants (SPEs) provide a direct comparison of the sorption efficiencies of different functional groups on a common solid support. A phosphorous-functionalized material, UiO-66-PO-Ph, with enhanced thermal stability (∼500 °C) exhibits the best sorption capacity (∼96%) in an acidic medium (pH 3). The parent MOF UiO-66-NH2 (92%) and iminopyridine-functionalized UiO-66-IMP (90%) showed excellent sorption in neutral conditions (pH 7). Amide-containing MOFs UiO-66-AM1 (40%), UiO-66-AMMal (31%) and UiO-66-AMGlu (70%), sulfur-based MOFs UiO-66-SMA (65%) and UiO-66-SSA (27%), and phosphorous-functionalized UiO-66-PO-OPh (50%) displayed maximum sorption in basic conditions (pH 8). The kinetics studies revealed rapid uranium sorption in about 2 h due to the effective binding of uranyl ions with the anchored functional groups of MOFs; quantitative elution of uranyl ions from the MOF framework was carried out with 0.1/0.01 M HNO3 . The MOFs also exhibit moderate recyclability for uranium sorption and can be regenerated by an acidic solution. The functionalized MOFs alter the stability in acidic/basic media; thus, UiO-66-NH2 is a versatile MOF material employed as an SPE for the extraction of radionuclides from aqueous media. This work also provides a platform for the development of new functionalized MOF materials for the efficient sorption of uranium as well as moderate recyclability for its removal, and the potential applications include the removal of uranium from aqueous waste streams.